Development of methods to measure the potential of a plaster to regulate indoor humidity. (September 2021) - Lim, Kiyomi D; Maskell, Daniel
Moisture buffering utilises hygroscopic construction materials as a more sustainable approach to passively moderate indoor humidity. This study seeks to develop a reproducible test method to obtain a moisture buffering value of common building materials under conditions that reflect typical indoor environmental conditions. Temperature and humidity variations in sinusoidal profiles for two different materials, typically used to finish internal surfaces, have been studied to identify their potential moisture regulation behaviour. Outcomes were then combined and ranked indicating the potential of materials to passively regulate the indoor humidity and the need for robust methods of investigation. Practical application: In response to current practice and materials' testing procedures, a reproducible test method is considered to enable comprehensive understanding of a hydroscopic materials' behaviour, where subsequent interpretation of their performance can be quantified. The practicality to consider the use of passive regulation using hygroscopic materials can then be justified to bring indoor RH closer to the optimal range without heavy reliance on mechanical solutions, achieving a more effective passive indoor climate monitoring. It is expected that the outcome of this investigation can potentially form the basis of further improvement on a standardised test method to obtain moisture buffering value of hygroscopic non-structural elements for pragmatic application during design integration process.